Preparation of Benzylamine by Highly Selective Reductive Amination of Benzaldehyde Over Ru on an Acidic Activated Carbon Support as the Catalyst - Gomez, Silvia; Peters, Joop A.; van der Waal, Jan C.; Zhou, Wuzong; Maschmeyer, Thomas (Catalysis letters, 2002)
Ruthenium supported on activated carbon, on which acidic groups were introduced by pre-treatment with (NH4)2S2O8, is a highly active and selective catalyst for the synthesis of benzylamine via the reductive amination of benzaldehyde.